Measurement with the ATLAS detector of multi-particle azimuthal correlations in p + Pb collisions at √sNN= 5.02 TeV - Alonso, Francisco (2013)
In order to study further the long-range correlations ("ridge") observed recently in p + Pb collisions at √sNN= 5.02 TeV, the second-order azimuthal anisotropy parameter of charged particles, v2, has been measured with the cumulant method using the ATLAS detector at the LHC. In a data sample corresponding to an integrated luminosity of approximately 1 μb-1, the parameter v2has been obtained using two- and four-particle cumulants over the pseudorapidity range |η|<2.5. The results are presented as a function of transverse momentum and the event activity, defined in terms of the transverse energy summed over 3.1 < η <4.9 in the direction of the Pb beam. They show features characteristic of collective anisotropic flow, similar to that observed in Pb + Pb collisions. A comparison is made to results obtained using two-particle correlation methods, and to predictions from hydrodynamic models of p +Pb collisions. Despite the small transverse spatial extent of the p + Pb collision system, the large magnitude of v2and its similarity to hydrodynamic predictions provide additional evidence for the importance of final-state effects in p + Pb reactions.